THE IMPACT OF KNOWLEDGE RESOURCE COMPETENCIES IN ACHIEVING ORGANIZATIONAL AGILITY: AN EXPLORATORY STUDY ON A SELECTED SAMPLE OF WORKERS IN THE DIRECTORATE OF EDUCATION OF NAJAF - Dr. Mohammed Saleh Mahdi (Scholar Express Journal, 2023)
The study aimed to identify the capabilities of the knowledge resource in the General Directorate of Education in the province of Najaf, which qualifies them to manage knowledge processes to reach organizational agility. Najaf, the researcher used the exploratory analysis approach to reach the results, and the researcher used the program (SPSS.V.24). The study concluded that there is an influence relationship between intellectual ability through creative thinking and the ability to realize the requirements of work and logical conclusion through the search for information on achieving organizational agility in solving problems and sensing environmental stimuli, and came out with the most important recommendations adequate attention to personal relationships between individuals by providing a psychological and organizational atmosphere It is based on love, affection, and mutual trust..
Keywords: knowledge resource Competencies; organizational agility